Adverse Reactions Associated with Systemic Polymyxin Therapy. Issue 1 (30th September 2014) - Justo, Julie Ann; Bosso, John A.
<x xml:space="preserve">Abstract</x> The systemic polymyxins, colistin and polymyxin B, are increasingly used for multidrug‐resistant bacterial infections and have a long history of dose‐limiting toxicity. This review summarizes the most recent available information about the mechanisms, incidence, risk factors, and minimization strategies for polymyxin toxicity. Nephrotoxicity is related to polymyxin exposure with both size of dose and length of therapy associated with frequency. Newer studies have questioned conventional thinking that the relative risk of nephrotoxicity is lower for colistin than polymyxin B, especially in light of evolving dosing practices. Neurotoxicities and hypersensitivity reactions are less common than nephrotoxicity. New techniques to minimize or avoid polymyxin toxicities are now emerging including a growing interest in clinical assays for therapeutic drug monitoring and the development of novel, less toxic agents (e.g., polymyxin derivatives) for the treatment of multidrug‐resistant bacterial infections.